SOCIAL STATUS DETERMINATION IN THE LAW ENFORCEMENT SYSTEM AT INDONESIA - Laboure, Katharina Zoe; Saputra, Edwin Puguh; Fauzi, M. Asif Nur (JURNAL SETIA PANCASILA, 2024)
Justice in the Indonesian legal system has been the subject of complex debate, especially in terms of views on individual social status. This article aims to explore the role of social status in the Indonesian judicial process, as well as its impact on justice and public trust in the legal system. By analyzing a variety of cases and legal approaches, this article provides an in-depth look at how social status can influence the justice process, including the determination of punishment and treatment in court. Through this analysis, we can understand the complex dynamics involved in the Indonesian justice system and identify challenges and opportunities to improve justice in the context of social status. This research provides important insights for policy makers, legal practitioners, and the public in efforts to strengthen the principles of justice in the Indonesian legal system.